Widespread diminishing anthropogenic effects on calcium in freshwaters - Weyhenmeyer, Gesa A; Hartmann, Jens; Hessen, Dag O; Kopáček, Jiří; Hejzlar, Josef; Jacquet, Stéphan; Hamilton, Stephen K; Verburg, Piet; Leach, Taylor H; Schmid, Martin; Flaim, Giovanna; Nõges, Tiina; et al. (Scientific reports, 2019)
Calcium (Ca) is an essential element for almost all living organisms. Here, we examined global variation and controls of freshwater Ca concentrations, using 440 599 water samples from 43 184 inland water sites in 57 countries. We found that the global median Ca concentration was 4.0 mg L-1 with 20.7% of the water samples showing Ca concentrations ≤ 1.5 mg L-1, a threshold considered critical for the survival of many Ca-demanding organisms. Spatially, freshwater Ca concentrations were strongly and proportionally linked to carbonate alkalinity, with the highest Ca and carbonate alkalinity in waters with a pH around 8.0 and decreasing in concentrations towards lower pH. However, on a temporal scale, by analyzing decadal trends in >200 water bodies since the 1980s, we observed a frequent decoupling between carbonate alkalinity and Ca concentrations, which we attributed mainly to the influence of anthropogenic acid deposition. As acid deposition has been ameliorated, in many freshwaters carbonate alkalinity concentrations have increased or remained constant, while Ca concentrations have rapidly declined towards or even below pre-industrial conditions as a consequence of recovery from anthropogenic acidification. Thus, a paradoxical outcome of the successful remediation of acid deposition is a globally widespread freshwater Ca concentration decline towards critically low levels for many aquatic organisms.